Pelanggaran Prinsip Kerja Sama Sebagai Pembentuk Wacana Humor Pada Tuturan Dialog Wayang Kampung Sebelah Di MNC TV Dan Implikasi Pembentuk Teks Anekdot Sebagai Bahan Ajar Di SMA - Nugrahanto, Bagus Ajie; , Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
Language is the main tool used by man to cooperate well. In cooperation principle, if someone obey that principle the commnication will run well, conversely if someone break them so that the contribution needed is not appropriate with the need by our opponent to talk with. The aim of this reseacrh is to describe the kinds of cooperation principle infringement happen in the scene of "WayangKampungSebelah", to describe the certain purposes and intentions from every single infringement done by puppet actors as well. This research used qualitative descriptive. The subject of this research is the pronounciation in the scene of WayangKampungSebelah. The data, then was analyzed by qualitative descriptive paradigm.In conclusion, this research found four cooperation principle infringements.The biggest number of infringement happen in maxim quantity with 11 data, infringement of maxim quality with 8 data, infringement of maxim relevance with 6 data, while the mininum number happen in infringement of maxim manner with 5 data. Besides those infringements, there were purpose or intention done such as satire, stricture, and make jokes or humor. Based on humor appeared from maxim infringement, it can be used and be implemented in the form of anekdote text as the teaching material for senior high school students. Key words: language, infringement, cooperation principle, maxim, teaching material